Judicial Review and Civil Society Oversight: Synergy in Realizing a Demo-cratic Constitutional Court (Study of Constitutional Court Decision Number 90/PUU-XXI/2023) - Khilmi, Erfina Fuadatul (LEGAL BRIEF, 2025)
The intervention of political power in judicial review has a significant impact on the constitutional court, which is considered to disrupt the independence of constitutional judges and the pattern of constitutional interpretation in line with power. Although, the resulting decision opens up opportunities for people's constitutional rights, it does not fully favour the power of the community as a counterweight in judicial review. The research method used is normative juridical with a conceptual approach, a statutory approach and a case approach to Constitutional Court Decision Number 90/PUU-XXI/2023. This study aims to analyze Judicial Review and civil society oversight that work together in realizing democratic judicial decisions in the midst of political forces that intervene in constitutional courts in Indonesia. The results show that in a judicial review that has been intervened by political forces, public access to the judicial review process has been controlled by political interests. Therefore, the importance of special arrangements regarding the amicus curiae mechanism of public participation is a form of democratic control in a state of law to provide opinions as additional considerations for judges which should be part of the formal procedures in judicial review. This is done while still ensuring the protection of the constitutional rights of the community actively and objectively in the decisions produced by the Constitutional Court.